MAKING SUDOKU PUZZLES LEARNING MEDIA ON ELEMENTS PERIODIC SYSTEM MATERIALS - Supyan Sauri; Cucu Zenab Subarkah; Sari Sari (UIN Sunan Gunung Djati Bandung, 2021)
Sudoku Puzzles is one of the educational game learning media which has advantages, one of which is being able to develop ways of reasoning, thinking correctly according to logic. One of the chemical concepts that requires this medium is the Periodic System of the Elements material. This study aims to analyze the validation test of Sudoku Puzzles learning media products on the Elements Periodic System material and describe the appearance of Sudoku Puzzles learning media products on the Elements Periodic System material. The stages of this research use the Design Base Research (DBR) method to develop Sudoku Puzzles learning media on the Elementary Periodic System material as a learning process that can challenge students through a game. This research procedure uses the ADDIE model consisting of several stages including Analysis, Design, and Development. Based on theinstruments used, namely flowcharts and storyboards, the Sudoku Puzzles learning media was made, then validation tests were carried out on three validators, namely media experts, learning experts and content experts.The validation result data shows a value of 0.89, thus the Sudoku Puzzles learning media is declared valid and can be used as a tool in the learning process of the Elements Periodic System material.